2005
DOI: 10.1108/14777280510590031
|View full text |Cite
|
Sign up to set email alerts
|

Positive leadership yields performance and profitability

Abstract: PurposeTraditional management techniques and change management interventions are deficit‐based. That is, they often focus on “fixing” what is wrong in our organizations by solving problems. Maintaining a committed and motivated workforce, open to learning, growth and positive change, is difficult, however, when the daily focus is on what's not working.Design/methodology/approachGrowing evidence suggests that positive leadership and a strengths‐based approach to long‐term organizational change have a greater im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Publicly recognizing team achievements helps in providing cohesive team efforts and productivity (Levi & Askay, 2020). Team rewards are most effective when organizations link performance with organization mission and purpose, customer satisfaction, and the contribution to profitability (Tombaugh, 2005). The practical reality of rewarding team efforts and achievements mirrors the fact that results are ultimately achieved by integrated efforts (Deming, 2000).…”
Section: Reward Team Achievementsmentioning
confidence: 99%
“…Publicly recognizing team achievements helps in providing cohesive team efforts and productivity (Levi & Askay, 2020). Team rewards are most effective when organizations link performance with organization mission and purpose, customer satisfaction, and the contribution to profitability (Tombaugh, 2005). The practical reality of rewarding team efforts and achievements mirrors the fact that results are ultimately achieved by integrated efforts (Deming, 2000).…”
Section: Reward Team Achievementsmentioning
confidence: 99%
“…Furthermore, the findings of the current study have shown a statistically-significant as well as a practically-significant positive relationship between the PsyCap construct of optimism and organisational commitment and the subdimensions of normative commitment and affective commitment. Research studies have shown that optimism is related positively to employee engagement and employee performance (Medlin & Faulk, 2011;Tombaugh, 2005). In addition, Bressler (2010) found that optimism had a positive relationship with affective commitment.…”
Section: Inferential Statisticsmentioning
confidence: 99%
“…Positive leadership influences the organizational culture and can, consequently, stimulate productivity. 57 Certain leadership patterns can be crucial in the current situation to encourage the search for creative and innovative solutions in the midst of the crisis. A study carried out in Turkey used questionnaires to evaluate the relationship between authentic leadership (AL) and the innovation capacity of 142 employees from different sectors.…”
Section: Discussionmentioning
confidence: 99%